STUDENT PERCEPTION ON BUSINESS ETHICS - Suwardi, Eko; Artiningsih, Arika; Novmawan, M. Ridwan (Journal of Indonesian Economy and Business, 2014)
Many research conducted on the behavior of business persons and their perception on businessethics. However, rarely similar study deals with the perception of students on businessethics. Indeed, students are our future generation who are going to have substantial role inIndonesian business and economy. Therefore this study focuses on students as a proxy for futurebusiness players in this country (Trawick and Draden, 1980). We compare among groups ofstudents based on their maturity, formal business ethic education, gender and specific professionalbackgrounds. The results of analysis show that in general students have good perceptionon business ethics. Further, there is a significant different perception on business ethics amongstudents with different academic maturity, professional background. Student with businessbackground are less ethical compare to those are with non-business background. This may consistentwith previous evidence found that ethical principles need to be introduced more tobusiness students. In contrast, there is no different perception on business ethics among studentwith different gender groups and formal business ethics course. This could be business ethicsformal education takes time to be internalized by participants or student with no formalbusiness ethics course also learn business ethics from other sources.Keywords: students, perceptions, business ethics